Building professional development opportunities in data services for academic librarians. (March 2017) - Conrad, Suzanna; Shorish, Yasmeen; Whitmire, Amanda L.; Hswe, Patricia
Research data management represents a significant professional development area for academic librarians – significant for its growing importance to the profession, since researchers are increasingly expected to comply with research data management requirements, and for the extent of competence needed by librarians to support researchers in research data management practices and plans. This article recounts how the Association of College and Research Libraries is fostering professional development opportunities in research data management. The authors describe two key endeavors: (1) the development and deployment of a needs assessment survey, which allowed insight into the types of librarians expressing the most need; and (2) planning and implementation of a pre-conference workshop for ACRL 2015, intended to prototype a future professional development offering. The article concludes by discussing additional assessment that was done following the workshop and how the pre-conference laid the foundation for proposing a "roadshow" for research data management, similar to what the Association of College and Research Libraries sponsors for scholarly communication.